"I'm tired of being pulled from pillar to post": A qualitative analysis of barriers to mental health care for trauma‐exposed young people. Issue 1 (19th January 2020) - Ellinghaus, Carli; Truss, Katie; Liao Siling, Jocelyn; Phillips, Lisa; Eastwood, Oliver; Medrano, Carmen; Bendall, Sarah
Abstract: Aim: Traumatic experiences in childhood are pervasive and associated with a range of deleterious mental health outcomes. Despite this, trauma‐exposed young people often do not seek help from mental health services. While barriers to care for general mental health concerns are well established, less is known about those specifically facing young people who have experienced trauma. The present paper sought to examine the barriers in seeking mental health care faced by trauma‐exposed young people through a qualitative analysis of online forums where individuals discuss and seek informal support for trauma. Methods: This study used a qualitative, netnographic design, following the six‐step LiLEDDa framework, developed for the analysis of online forums. Posts about trauma written in 2016 from five Internet forums targeting young people were included and analysed via thematic analysis. Results: Barriers to mental health care for trauma‐exposed young people were categorized into two interrelated themes: (a) structural and (b) relational barriers. Structural barriers related to practical challenges faced when accessing and engaging with mental health services. Relational barriers focused on interpersonal relationships with mental health service providers and how these influenced experiences of, and consequent engagement with, services. Conclusions: Trauma‐exposed young people appear to experience multiple barriers to mental health care, whereby interactions between structural and relational barriers determine ongoing engagement. Service‐wide reform including trauma‐informed mental health training for practitioners is urgently needed to improve access to care and engagement for this vulnerable group.